DIGITAL MARKETING STRATEGIES FOR STARTUPS: A SYSTEMATIC LITERATURE REVIEW - Mahmudatun Hasanah (PT. Hasba Edukasi Mandiri, 2025)
This study explores the effectiveness of digital marketing strategies for startups, comparing them with traditional marketing approaches. In today’s competitive business landscape, digital marketing has become a crucial tool for startups due to its cost-effectiveness, scalability, and ability to provide measurable results. The research highlights key digital marketing strategies such as social media marketing, SEO, content marketing, and influencer collaborations, focusing on their ability to drive ROI, increase brand awareness, and foster customer engagement. The findings suggest that startups can significantly benefit from digital marketing due to its ability to precisely target audiences, track performance in real-time, and offer personalized customer experiences. In contrast, traditional marketing methods, while still relevant in certain contexts, lack the flexibility and data-driven capabilities that digital marketing provides. This study emphasizes the importance of adopting digital marketing strategies tailored to startups’ needs, and the necessity of staying adaptable in the rapidly evolving digital space.